2016
DOI: 10.4103/0970-9290.179808
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of 10% whole Azadirachta indica (neem) chip as an adjunct to scaling and root planning in chronic periodontitis: A clinical and microbiological study

Abstract: Hence, 10% neem oil local delivery system delivers desired effects on P. gingivalis. Further research is needed to evaluate the neem oil efficacy on other periodontal pathogens.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 1 publication
2
16
0
2
Order By: Relevance
“…Similar results were obtained using bark and twigs of the tree (Chaurasia, 2016;Geethashri, Manikandan, Ravishankar, & Shetty, 2014;Sundaram, Narayanan, & Vadakkepurayil, 2016). Moreover, nonabsorbable A. indica oil chip (10%) showed significant antibacterial properties against Porphyromonas gingivalis, a periodontal pathogen (Vennila, Elanchezhiyan, & Ilavarasu, 2016).…”
Section: Antibacterial Activitysupporting
confidence: 60%
See 1 more Smart Citation
“…Similar results were obtained using bark and twigs of the tree (Chaurasia, 2016;Geethashri, Manikandan, Ravishankar, & Shetty, 2014;Sundaram, Narayanan, & Vadakkepurayil, 2016). Moreover, nonabsorbable A. indica oil chip (10%) showed significant antibacterial properties against Porphyromonas gingivalis, a periodontal pathogen (Vennila, Elanchezhiyan, & Ilavarasu, 2016).…”
Section: Antibacterial Activitysupporting
confidence: 60%
“…Moreover, nonabsorbable A . indica oil chip (10%) showed significant antibacterial properties against Porphyromonas gingivalis , a periodontal pathogen (Vennila, Elanchezhiyan, & Ilavarasu, ).…”
Section: Pharmacological Attributesmentioning
confidence: 99%
“…38,39 Nimbidin and sodium nimbidate are the major components of neem responsible for most of its pharmacological actions. 31 It was observed that 5% of neem extract was effective against gram positive and gram negative bacteria in culture medium and 10% extract yielded better results in clinical studies. 31 In one recent study conducted by a group of periodontist a 10% non-absorbable neem chip was placed in the gingiva.…”
Section: Discussionmentioning
confidence: 99%
“…Our bibliographical review process covered a total of 16 publications including three books [37][38][39], and 13 scientific articles [32,[40][41][42][43][44][45][46][47][48][49][50][51]. One reference accounted for 81.4% of the 495 ethnobotanical uses recorded [37].…”
Section: Selection Of Plantsmentioning
confidence: 99%